2011
DOI: 10.1016/j.ijsu.2010.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative assessment of cardiac risk and perioperative cardiac management in noncardiac surgery

Abstract: More than 27 million Americans undergo noncardiac surgery annually. Cardiac complications can be a major source of morbidity and mortality in the perioperative period. Preoperative risk stratification, intraoperative ischemia monitoring and postoperative surveillance help to predict, identify and efficiently treat these adverse events. A renewed emphasis on preoperative evaluation has helped to identify patients at an increased risk for adverse cardiac events and thus, implement noninvasive or invasive cardio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 63 publications
2
13
0
Order By: Relevance
“…The RPP is a simple but important index that is an indirect indication of myocardial oxygen demand. An excessive rise in the RPP often accompanies the occurrence of myocardial ischaemia in patients with CHD . According to the results of the present study, intravenous dexmedetomidine reduced myocardial oxygen demand and improved myocardial ischaemic events, resulting in a decrease in perioperative complications in the study patients.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The RPP is a simple but important index that is an indirect indication of myocardial oxygen demand. An excessive rise in the RPP often accompanies the occurrence of myocardial ischaemia in patients with CHD . According to the results of the present study, intravenous dexmedetomidine reduced myocardial oxygen demand and improved myocardial ischaemic events, resulting in a decrease in perioperative complications in the study patients.…”
Section: Discussionsupporting
confidence: 66%
“…An excessive rise in the RPP often accompanies the occurrence of myocardial ischaemia in patients with CHD. 12 According to the results of the present study, intravenous dexmedetomidine reduced myocardial oxygen demand and improved myocardial ischaemic events, resulting in a decrease in perioperative complications in the study patients. In addition, we found that dexmedetomidine significantly improved ST segment and T wave changes, consistent with the experimental results of Jiang et al, 13 demonstrating that dexmedetomidine may decrease the stress response, reduce myocardial oxygen consumption and improve ischaemic myocardial function.…”
Section: Discussionsupporting
confidence: 53%
“…264 They can be caused by many different factors, ranging from simple vasodilation to cardiogenic shock 5.5.3.1. Postoperative hypotension/hypertension.…”
Section: Postoperative Haemodynamic Complications Acute Hfmentioning
confidence: 99%
“…Adherence to guidelines may be dependent on the convenience of use in clinical practice (DeHert, 2009). The ACC/AHA guidelines have several areas that lack clarity and are problematic because they are unclear (Barak et al, 2006;Hoeks et al, 2007). As an example, the ACC/AHA does not define "advanced age."…”
Section: Interventionmentioning
confidence: 99%
“…Preoperative cardiac assessment of the noncardiac surgical patient provides an opportunity to screen for previously unidentified cardiac comorbidities. Decision tools were developed by the ACC/AHA to assist with implementation of preoperative cardiac assessment practice guidelines (Fleisher et al, 2007;Fox, Moawad, & Music, 2003;Hoeks et al, 2007). The ACC/AHA clinical practicing guidelines represent the best evidence available for preoperative cardiac assessment for noncardiac surgery patients and can be used as an efficient preoperative cardiac assessment decision tool.…”
mentioning
confidence: 99%